Microfluidic-based solid phase extraction of cell free DNA. Issue 22 (19th October 2018) - Campos, Camila D. M.; Gamage, Sachindra S. T.; Jackson, Joshua M.; Witek, Malgorzata A.; Park, Daniel S.; Murphy, Michael C.; Godwin, Andrew K.; Soper, Steven A.
Abstract : Plastic microfluidic device for the efficient isolation (>90% recovery) of cell free DNA from plasma for molecular profiling. Abstract : Cell-free DNA (cfDNA) is a liquid biopsy marker that can carry signatures ( i.e., mutations) associated with certain pathological conditions. Therefore, the extraction of cfDNA from a variety of clinical samples can be an effective and minimally invasive source of markers for disease detection and subsequent management. In the oncological diseases, circulating tumor DNA (ctDNA), a cfDNA sub-class, can carry clinically actionable mutations and coupled with next generation sequencing or other mutation detection methods provide a venue for effective in vitro diagnostics. However, cfDNA mutational analyses require high quality inputs. This necessitates extraction platforms that provide high recovery over the entire ctDNA size range (50 → 150 bp) with minimal interferences ( i.e., co-extraction of genomic DNA), and high reproducibility with a simple workflow. Herein, we present a novel microfluidic solid-phase extraction device (μSPE) consisting of a plastic chip that is activated with UV/O3 to generate surface-confined carboxylic acid functionalities for the μSPE of cfDNA. The μSPE uses an immobilization buffer (IB) consisting of polyethylene glycol and salts that induce cfDNA condensation onto the activated plastic microfluidic surface. The μSPE consists of an array of micropillars to increase extraction bed load (scalable to loads >700 ng of cfDNA) and can be produced at low-cost using replication-based techniques. The entire μSPE can be fabricated in a single molding step negating the need for adding additional extraction supports to the device simplifying production and keeping device and assay cost low. The μSPE allowed for recoveries >90% of model cfDNA fragments across a range of sizes (100–700 bp) and even the ability to extract efficiently short cfDNA fragments (50 bp, >70%). In addition, the composition of the IB allowed for reducing the interference of co-extracted genomic DNA. We demonstrated the clinical utility of the μSPE by quantifying the levels of cfDNA in healthy donors and patients with non-small-cell lung and colorectal cancers. μSPE extracted cfDNA from plasma samples was also subjected to a ligase detection reaction (LDR) for determining the presence of mutations in the KRAS gene for colorectal and non-small cell lung cancer patients.